Inflammation and Hypoxia: HIF and PHD Isoform Selectivity. Issue 1 (January 2019) - Watts, Emily R.; Walmsley, Sarah R.
Abstract : Cells sense and respond to hypoxia through the activity of the transcription factor HIF (hypoxia-inducible factor) and its regulatory hydroxylases, the prolyl hydroxylase domain enzymes (PHDs). Multiple isoforms of HIFs and PHDs exist, and isoform-selective roles have been identified in the context of the inflammatory environment, which is itself frequently hypoxic. Recent advances in the field have highlighted the complexity of this system, particularly with regards to the cell and context-specific activity of HIFs and PHDs. Because novel therapeutic agents which regulate this pathway are nearing the clinic, understanding the role of HIFs and PHDs in inflammation outcomes is an essential step in avoiding off-target effects and, crucially, in developing new anti-inflammatory strategies. Highlights: Hypoxia signaling pathways are highly conserved between species and are ubiquitously expressed in mammalian cells. Activation of HIF has pleiotropic effects, and is under investigation as a potential therapeutic target in malignancy, ischemia, and inflammatory disease processes. Hypoxia and inflammation frequently coexist and may exacerbate one another. There are multiple and bidirectional links between the molecular pathways which sense and respond to hypoxia and inflammatory signals. Activation or inhibition of the HIF–PHD pathway is subject to fine-tuning through isoform-specific functions and expression profiles for different HIFs and PHDs. Early evidence from mouse studies supports the view that targeting this pathway may be therapeutic in inflammation, although the risks of off-target or side effects must be considered. Cautious optimism is urged.